Tendências granulométricas dos sedimentos de fundo no Rio Marrecas, região Sudoeste do Paraná - Luz, Constantino Eleuthério da (2011)
The dissertation examines the downstream finning phenomenon as it operates in the bottom sediments in the Marrecas river, located in South West region of Parana state, Brazil. The area of basin has 865,43 km2 and encompasses he municipalities of Francisco Beltrão, Marmeleiro, Flor da Serra do Sul, Verê and Itapejara D Oeste. The Marrecas river basin inserted in Cretaceous age rock composed of basaltic rocks of the Serra Geral Formation with plateaus characterized by dissecting medium and high, elongated tops and slopes convex and straight. Were calculated the main basin morphometric index based on 1:260,000 scale map and longitudinal thalweg profile of the main channel based on 1:50,000 scale topographic maps. The botton sediments samples was performed in December 2009 and January 2010 with a van Veen samples in a location preferably located in the vicinity of the main tributaries of Marrecas river and easy access to river banks. The sandy and coarse sediments were analyzed by sieving techniques and use of gravelometer device. Were calculated grain-size statistical parameters: mean, median, sorting, skewness and kurtosis as defined by Folk & Ward (1957). The sphericity of the coarse sediments was defined by adopting the classification of Zingg (1935). The trends observed particle size showed a clear downstream finning of botton sediments in the downstream direction, changed locally due to the contribution of sediments by tributaries. The sorting showed no trend with values ranged from moderately to very poorly. Skewness shows a trend of variation of positive values in the upper reaches of the Marrecas river for negative values in the lower reaches, while the kurtosis showed a slight tendency passing values platikurtic to leptokurtic. The predominance of spherical shape in bottom sediments was attributed to spheroidal weathering and low resistance to abrasion of the rock.